Penerapan Pendidikan Karakter pada Siswa untuk Meningkatkan Nilai-nilai serta Minat Belajar Siswa di SMK N 2 Panyabungan - Rosdanilah Rosdanilah; Novebri Novebri (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2025)
Character education plays an important role in forming students who are not only academically intelligent, but also have strong morals and positive behavior. Character education is a process of developing moral values, ethics and virtues to create individuals who are virtuous, responsible and able to respect human values. The main factor in character formation is oneself, but family and environment also have a crucial role. At SMK Negeri 2 Panyabungan, character education is implemented through the integration of character values in learning and extracurricular activities, supported by collaborative learning methods that teach cooperation, responsibility and empathy. The implementation of character education has been proven to increase student learning motivation, discipline and interest in learning. Values such as honesty, hard work and discipline are involved in learning activities and are internalized by students through direct experience and example from teachers. Strengthening this character also reduces the level of delinquency and conflict at school, creates a conducive learning environment and supports students’ personal development. Consistent character education has a positive impact, both on academic aspects and on the formation of attitudes and behavior needed in the world of work and social life. In this research, it is found that education has an important role in forming character and increasing students’ interest in learning. This research aims to analyze the application of character education in improving the moral values, ethics and learning motivation of students at SMK Negeri 2 Panyabungan. Character education is integrated through innovative approaches such as project-based learning, involving schools and families in forming children’s character. The research results show that character education significantly supports students’ personality development, increases interest in learning, and helps them face life’s challenges positively.